Isolation of Neural Stem Cells from Whole Brain Tissues of Adult Mice. (5th February 2019) - Deshpande, Krutika; Saatian, Behnaz; Martirosian, Vahan; Lin, Michelle; Julian, Alex; Neman, Josh
Abstract: A population of neural stem cells exists in the adult mammalian central nervous system. Purification and characterization of neurospheres provide valuable tools to study the regulation and differentiation of neural stem cells both in vitro and in vivo . Successful stimulation and production of neurospheres can ultimately be used for therapeutic purposes. The currently available methods are limited by their poor yield and the large number of animals required to compensate for that. Here, we describe a procedure to purify neurospheres from adult mouse whole brain. We provide detailed steps on how to propagate, passage, and maintain the adult neurospheres, and how to differentiate the pure neurospheres into the lineage of interest. Using this method, neurospheres can be easily derived from adult mouse whole brain. The derived adult neurospheres maintain their homogenous undifferentiated status while retaining their differentiation potential. This new protocol facilitates adult neurospheres isolation, purification, maintenance, and differentiation. © 2019 by John Wiley & Sons, Inc.